Acquired motility of Babesia microti –infected red blood cells - Chao Li; Amy L. Apgar; Danielle M. Tufts; Tagbo H. R. Niepa (Proceedings of the National Academy of Sciences, 2026)
Babesia microti is an intraerythrocytic protozoan parasite and the main causative agent of human babesiosis in the United States. While extensive research has focused on the prevalence of this vector-borne pathogen in natural populations, increases of human cases and clinical manifestation, and pathogen structure, little is known about the movements of B. microti within vertebrate red blood cells (RBCs). RBCs are nonmotile due to their lack of cellular structures for active movement. Here, we report a phenomenon in which B. microti –infected RBCs exhibit an acquired motility compared to uninfected RBCs. Using live-cell tracking, we observed a subset (around 1% in whole blood and 10% in 1:100 diluted blood) of infected RBCs displayed active movement. This acquired motility suggests that B. microti may induce host cell modifications that facilitate its survival, dissemination, or immune evasion potential, allowing it to successfully move through the blood and infect new RBCs. Our findings highlight unconventional RBC dynamics and a potential broad aspect of B. microti pathogenesis. Further investigation into the molecular mechanisms underlying this phenomenon could provide insights into parasite–host interactions and reveal targets for therapeutic intervention in treatment and/or prevention of babesiosis.